Treatment Of Palatoplasty Repair With Von Langenbeck Technique And Hemostatic Absorbable Gelatin: Case Report And Literature Reviews - Ibnu Ikhsan, M. Idris; Subarno, Saktrio D. (Jurnal Plastik Rekonstruksi, 2019)
Background: Cleft is a common congenital abnormality in the lip and palate. Cleft palate or palatoschisis is a congenital abnormality occured during pregnancy, resulting in cleft of the palate that does not coalesce into the nasal cavity area, so there is a relationship between the nasal cavity and mouth. Various surgical techniques for cleft palate correction can be used and each method has advantages and disadvantages. Patient and Method: Here, we report a case of palatoschisis reconstruction using Von Langenbeck technique and hemostatic absorbable gelatin that was carried out at Aliyah 3 Hospital, Kendari. Result: After initial diagnosis, the patient underwent surgery about two weeks later. Von Langenback palatoplasty was performed to close the palate defect. The defect then closed primarily with 4/0 optime and 6/0 corolene. Conclusion: Optimal surgical planning, good patient orientation and surgical techniques that are carefully considered are essential for optimal results. Herein, we report a case of palatoschisis and reconstructive surgery using von Langenback technique performed to restore the cleft of palate.